Characterization of microbial community and antibiotic resistome in intra urban water, Wenzhou China - Ye, Sheng; Li, Shengkai; Su, Chenjun; Shi, Zhuqing; Li, Heng; Hong, Jiawen; Wang, Shengke; Zhao, Jingyan; Zheng, Weiji; Dong, Shixuan; Ye, Shuhan; Lou, Yongliang; et al. (Frontiers in Microbiology, 2023)
Abstract The present study investigated the microbial composition and accumulation of antimicrobial resistance genes in urban water habitats. Metagenomic analyses were conducted on 20 locations, including hospital surroundings (n=7), community rivers (n=7), and natural wetlands (n=6). Results showed that water samples collected near hospitals had higher concentrations of nitrogen and phosphate, which were associated with higher gene abundances for nitrate and phosphate degradation compared to community and wetland settings. They also had a higher abundance and diversity of clinical pathogenic bacteria and antimicrobial resistance genes (ARGs), with aminoglycoside, beta-lactam, and tetracycline being the most prevalent. Spearman correlation analysis indicated that plasmids and integron intI1 may be responsible for the mobilization of ARGs in the water samples. Given the sanitary conditions in the region, further surveillance is necessary to monitor antimicrobial resistance and the potential transmission of multidrug-resistant bacteria between humans and the hospital surroundings. This study highlights the importance of public health initiatives aimed at mitigating the spread of antibiotic resistance.